Diagnóstico da aprendizagem: uma forma produtiva e eficaz de realizá-lo - Kellner, Sheilah Rubino de Oliveira (1976)
The main goal of this study is to evaluate the adequability of the confidence testing scoring system as an evaluation method of the students' performance, both individually and in group. It is understood that this system leads to reliable informations which are to be considered in the decision-making process in teaching and learning. It is shown that the present scoring-system provides • better conditions to undertake remedial measures as it leads to informations about the extent of know-ledge aquired; students' deeper engagement in the evaluation process; • possibility of identifying the student's knowledge level and/or abilities gained. Henceforth it presents · the oportunity of tracing distortions of the students' self-image perceptions, which occur in the learning process. The adequability of the system is re-assured by the results at first. The advantages of applying the present scoring system to objective tests (multiple-choice items) allow the author to suggest its use as an evaluation system of the examinee content information level.